Vaccination in the elderly: an immunological perspective - Chen, Wilbur H.; Kozlovsky, Bernard F.; Effros, Rita B.; Grubeck-Loebenstein, Beatrix; Edelman, Robert; Sztein, Marcelo B. (Trends in immunology, 2009)
Successful vaccination of the elderly against important infectious pathogens that cause high morbidity and mortality represents a growing public health priority. Building on the theme of aging and immunosenescence, we review mechanisms of human immunosenescence and the immune response to currently licensed vaccines. We discuss the difficulties in identifying the risk factors that, in addition to aging, cause immunosenescence and address the relative paucity of vaccine studies in the elderly. We conclude that vaccine responses are blunted in the elderly compared with that of healthy young adults. However, it is also clear that our understanding of the mechanisms underlying immunosenescence is limited and much remains to be learned to improve the effectiveness of next generation vaccines.